SCREENING OF ANTI-MRSA ACTIVITY OF SOME SELECTED TRADITIONAL DRUG FORMULATIONS AGAINST DIABETIC FOOT ULCER ISOLATES - SAREENA C,; SUCHITHRA T V, (International Journal of Pharma and Bio Sciences, 2014)
Methicillin resistant Staphylococcus aureus (MRSA) is a well known superbug commonly responsible for wound-related infections and most ominously for its life-threatening conditions. The MRSA infections are great medical challenges in diabetic patients, especially causing ulcer foot infections and related complications which might lead to amputation and ultimately to death. The alarming increase in drug-resistant bacteria makes it a global concern and the need to find novel drugs imperative. In the present study, an anti–MRSA screening was performed to substantiate the antibacterial activity of some selected ayurvedic traditional preparations used as a topical application for skin infections and wound healing. Jatyadi taila, kanjunniadi taila, durvadi taila, and murivenna were subjected for this study. Among the studied samples, jatyadi taila and kanjunniadi taila have shown significant anti-MRSA activity.